Pengaruh Inflasi dan Nilai Tukar terhadap Pertumbuhan Ekonomi dengan Penerimaan Pajak sebagai Variabel Moderasi - Icha Restiasanti; Indah Yuliana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This empirical study aims to prove the effect of inflation and exchange rates on economic growth with tax revenue as a moderating variable in 2011-2020. This study uses secondary data, namely time series data from the website of the Central Statistics Agency and Bank Indonesia from 2011-2020. Quantitative research is a type of research that is taken in this study. This study uses multiple linear regression data analysis techniques and regression analysis with moderating variables (Moderating Regression Analysis) using the Eviews 12 program. The results prove that inflation has a negative but not significant effect on economic growth in Indonesia. The exchange rate has no significant effect on economic growth in Indonesia. Tax revenue as a moderator homologiser or potential moderator between inflation and economic growth. This means that the variable of tax revenue as a moderating variable does not interact with inflation so that it is not significantly related to economic growth. Tax revenue is also a moderator of the homologiser or potential moderator between the exchange rate and economic growth. This means that the variable of tax revenue as a moderating variable does not interact with the exchange rate so that it is not significantly related to economic growth. Keywords: inflation, exchange rate, tax revenue, economic growth